Intestinal Guanylate Cyclase-C mRNA Expression in Duodenum and Colon of Children. Issue 6 (December 2021) - Cohen, Mitchell B.; Gold, Benjamin D.; Xanthakos, Stavra A.; CaJacob, Nicholas; Weissman, Taryn; Bartolini, Wilmin; Boinpally, Ramesh; Mallick, Madhuja; Reasner, David S.; O'Dea, Christopher R.; Kwak, Hanna; Ge, Pei
ABSTRACT: Objectives: Guanylate cyclase-C (GC-C) agonists, which increase intestinal secretion and accelerate transit, are used to treat chronic constipation and constipation-predominant irritable bowel syndrome and are being evaluated for pediatric use. Prior studies suggest GC-C receptor density may be higher in young children, potentially amplifying GC-C agonism with treatment implications. We aimed to quantitate duodenal and colonic GC-C mRNA expression in children. Methods: Mucosal biopsies were obtained from subjects aged 6 months to 18 years during clinically indicated upper, that is, esophago-gastro-duodenal, and/or colonic endoscopy. Tissue samples without histologic abnormalities were grouped by subject age (<24 months, 24 months to <6 years, 6 to <12 years, and 12 to <18 years) and analyzed for GC-C mRNA expression by qPCR. The relationship between GC-C mRNA levels and age was modeled using regression analyses. Results: Ninety-nine subjects underwent upper endoscopy/colonoscopy; 93 had evaluable samples. Mean relative GC-C mRNA expression was 2.36 (range 2.21–2.46) for duodenal samples and 1.56 (range 1.22–1.91) for colonic samples. Predicted and observed normalized GC-C mRNA expression in each region were comparable among age groups. Pooled expression by region demonstrated lower expression in colonic versus duodenal samples. Conclusions: Uniform levels of GC-C mRNA expression were detected in children aged >6 months in the duodenum and >12 months in the colon. Higher expression was observed in all age groups in duodenal versus colonic samples, indicating regional variability in GC-C receptor density. These data are reassuring for further studies of GC-C agonists in children. Abstract : Supplemental Digital Content is available in the text